Jurnal ANALISIS PERAN MEDIA SOSIAL DALAM PROSES MEDIATISASI POLITIK: PERSPEKTIF KOMUNIKASI POLITIK DAN PARTISIPASI PUBLIK - Andzani , Diva; Virgin, Diah; Pristica , Bela; Dwihadiah , Desideria L (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract This study aims to analyze the role of social media in the process of political mediatisation, considering perspectives from political communication and public participation. The theories employed in the analysis include Mediatisation Theory, Political Communication Theory, Public Participation Theory, Algorithm and Filter Bubble Theory, and Fake News Dissemination Theory. The research method utilized is a qualitative approach through social media content analysis. Data were obtained from materials posted on social media by politicians, political parties, and citizens. The analysis results indicate that social media significantly influences political communication by facilitating direct interaction between politicians and voters, as well as enhancing public participation in political discussions. However, challenges such as the spread of fake news and political polarization also arise. In conclusion, it is recommended to enhance digital literacy among the public, monitor the use of social media by political actors, and involve educational institutions in political education to mitigate the negative impacts and enhance the positive benefits of social media use in politics. Keywords: Social media, Political mediatisation, Political communication, Public participation, Fake news dissemination